Inviting and initiating youth into a life of discipleship - Nel, Malan (Verbum et ecclesia, 2009)
The research question/problem with which this article deals is whether we have lost the radical nature of the faith community as disciples of Jesus and seekers of the Kingdom of God? In youth ministry children and adolescents are often invited to make a decision for Christ as if such a decision comprises the totality of being a Christian. Being a Christian, as with being a disciple, consists of more than a mere decision. Both the Old and New Testaments reveal greater depth to such a commitment. Discipleship involves following Christ in a more considered way. Such a commitment requires the willingness to be initiated and guided into the acquisition of wisdom which enables one to discern what the more appropriate options are for a Christian to make. Given such a positioning, the role of the faith community as a people demands consideration. This article argues that we are the invitation and recommends how to frame the invitation.